2019
DOI: 10.1371/journal.pone.0211756
|View full text |Cite
|
Sign up to set email alerts
|

DNA aptamers for the recognition of HMGB1 from Plasmodium falciparum

Abstract: Rapid Diagnostic Tests (RDTs) for malaria are restricted to a few biomarkers and antibody-mediated detection. However, the expression of commonly used biomarkers varies geographically and the sensibility of immunodetection can be affected by batch-to-batch differences or limited thermal stability. In this study we aimed to overcome these limitations by identifying a potential biomarker and by developing molecular sensors based on aptamer technology. Using gene expression databases, ribosome profiling analysis,… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 63 publications
1
12
0
Order By: Relevance
“…There is a critical need for a better understanding of malaria as well as tests for the rapid diagnosis and surveillance of malaria. As such, there have been many reports describing the selection of new aptamers 3,4,11,[58][59][60][61] to malaria targets as well as novel aptamer-based biosensors [62][63][64] . Previous studies generating aptamer probes to the IE surface have used pre-defined Plasmodium recombinant protein fragments or intact IEs and sophisticated microfluidic fabrication.…”
Section: Discussionmentioning
confidence: 99%
“…There is a critical need for a better understanding of malaria as well as tests for the rapid diagnosis and surveillance of malaria. As such, there have been many reports describing the selection of new aptamers 3,4,11,[58][59][60][61] to malaria targets as well as novel aptamer-based biosensors [62][63][64] . Previous studies generating aptamer probes to the IE surface have used pre-defined Plasmodium recombinant protein fragments or intact IEs and sophisticated microfluidic fabrication.…”
Section: Discussionmentioning
confidence: 99%
“…To validate the molecular binding affinity of the candidate sequences and protein, we used ZDOCK, which is a computational simulation tool for measuring molecular interactions (note that the docking simulation was not used in the generation of candidate sequences in Apta-MCTS). ZDOCK is commonly used in many molecular interaction studies, such as the theoretical molecular interactions between aptamers and HMG-box Pf [ 37 ].…”
Section: Methodsmentioning
confidence: 99%
“…To detect PfGDH in serum samples, they 1) coupled this aptamer with carbon dots as the probe 219 , 2) coupled the aptamer with dye as the catcher for an enzyme-catalyzed reaction 220 , and 3) applied this aptamer as the capture in a field-effect transistor biosensor 221 , resulting in detection limits of 2.85 nM, 63.97 pM, and 48.6 pM, respectively. For rapid diagnostic tests for Plasmodium infection, Joseph et al identified high mobility group box 1 protein (HMGB1) as a biomarker for Plasmodium infection using gene expression databases, ribosome profiling analysis, and structural modeling 222 . Later, they immobilized biotinylated HMG-box onto streptavidin-coated magnetic beads for protein-SELEX and developed several DNA aptamers of potential use for malaria diagnosis.…”
Section: Potential Utility Of Aptamer Technology For Pathogen Detectionmentioning
confidence: 99%